The training of social workers in the 40's decade from the career of Dr. Emilio Sánchez Rizza (Papeles, 2025)
This paper examines the career of Dr. Emilio Sánchez Rizza with the aim of contributing to the analysis and interpretation of the configuration of Social Work in the province of Santa Fe. His extensive academic, scientific and public service career in different positions, gives relevance to his figure as a central agent in the technical-bureaucratic formation of the State of Santa Fe and in the process of professionalization of the Social Service during the 40s. From this exposition, we seek to examine his influence and reconstruct the links with agents belonging to different fields (political, religious, academic) who participated in the process of professionalization of the Social Service. To this end, publications by Sánchez Rizza are identified, as well as sources corresponding to this historical period such as magazines, bulletins of public organizations and newspapers of the time, among others.
Keywords: Social Work; Vocational Training; Higher Education; Catholic Church; Politics